Olfactomedin proteins: central players in development and disease - Anholt, Robert (Frontiers in Cell and Developmental Biology, 2014)
Olfactomedin proteins are characterized by a conserved domain of 250 amino acids corresponding to the olfactomedin archetype first discovered in olfactory neuroepithelium. They arose early in evolution and occur throughout the animal kingdom. In mice and humans olfactomedin proteins comprise a diverse array of glycoproteins, many of which are critical for early development and functional organization of the nervous system as well as hematopoiesis. Olfactomedin domains appear to facilitate protein-protein interactions, intercellular interactions, and cell adhesion. Several members of the family have been implicated in various common diseases, notably myocilin in glaucoma and OLFM4 in cancer. This review highlights this important, hitherto understudied family of proteins.